2016
DOI: 10.1007/s11427-016-5076-8
|View full text |Cite
|
Sign up to set email alerts
|

A euryarchaeal histone modulates strand displacement synthesis by replicative DNA polymerases

Abstract: Euryarchaeota and Crenarchaeota, the two main lineages of the domain Archaea, encode different chromatin proteins and differ in the use of replicative DNA polymerases. Crenarchaea possess a single family B DNA polymerase (PolB), which is capable of strand displacement modulated by the chromatin proteins Cren7 and Sul7d. Euryarchaea have two distinct replicative DNA polymerases, PolB and PolD, a family D DNA polymerase. Here we characterized the strand displacement activities of PolB and PolD from the hyperther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Both PabPolD and PabPolB can extend DNA primers, with PabPolD requiring PabPCNA for efficient DNA synthesis. PabPolD conversely exhibits DNA strand displacement activity in the absence of PabPCNA, but PabPolB requires PabPCNA for this activity [47,48], with strand displacement activity inhibited for both polymerases in P. furiosus by the HPfA1 histone protein [49]. Only PabPolD can extend RNA primers, with RNA strand displacement only occurring for PabPCNA-stimulated PabPolD [47], suggesting a role for PolD in initial extension of primed templates on both leading and lagging strands.…”
Section: Euryarchaeotal Replication: Current Statusmentioning
confidence: 99%
“…Both PabPolD and PabPolB can extend DNA primers, with PabPolD requiring PabPCNA for efficient DNA synthesis. PabPolD conversely exhibits DNA strand displacement activity in the absence of PabPCNA, but PabPolB requires PabPCNA for this activity [47,48], with strand displacement activity inhibited for both polymerases in P. furiosus by the HPfA1 histone protein [49]. Only PabPolD can extend RNA primers, with RNA strand displacement only occurring for PabPCNA-stimulated PabPolD [47], suggesting a role for PolD in initial extension of primed templates on both leading and lagging strands.…”
Section: Euryarchaeotal Replication: Current Statusmentioning
confidence: 99%
“…8,9 In general, SDDS shows a lower processivity and rate compared with primer extension (PE). 10,11 Previous studies have revealed that high GC content 12,13 and protein binding 14,15 in the downstream duplex inhibits SDDS. Recently, our group has identified that DNA polymerase gp90 from Pseudomonas aeruginosa phage 1 (PaP1) is an A-family processive DNA polymerase containing 3′-5′ Exo activities.…”
Section: Introductionmentioning
confidence: 99%
“…These histones appeared to act as the major chromatin protein by forming extended polymeric structures that wrap DNA in multiples of 30-60 bp. Like eukaryotic histones, in some species archaeal histones have been shown to influence global transcription levels by hindering initiation (15) or elongation (16). Archaeal histones can also inhibit the binding of site-specific transcription factors (TFs) through competition (17).…”
Section: Introductionmentioning
confidence: 99%